Centesimal age and relative age effect in elite futsal players - Carraco, D. D. d. S.; Galatti, L. R.; Massa, M.; Loturco, I.; Abad, C. C. C. (International Journal of Exercise Science, 2020)
To investigate centesimal age (CA) and relative age effect (RAE) in elite male futsal players their date of birth and court-position were accessed through the official FIFA website. The absolute and relative frequency distributions of player births were quantified by quartiles and semesters. The two-way ANOVA and the Chi-Square analysis were applied to check for possible differences. The results showed a mean CA of 27.76 ± 4.11 years with no differences for both playing positions and competitions. In addition, no significant differences were found between quartiles or between semesters. The results suggest that elite male futsal athletes reach optimal competitive performance close to 27 years. Neither playing position nor geographical location may affect RAE, which seems to not affect the competitive performance (ranking) of elite male futsal players. These findings may help practitioners to understand the RAE phenomenon in futsal. In conclusion, being born in the early months of the year appears not to be important to successful performances in futsal. Overall, futsal athletes take about two decades to achieve their best performance. Coaches and researchers should consider the implementation of long-term training strategies (»20 years) to progressively and effectively develop young futsal players.